Extractable and dissolved soil organic nitrogen – A quantitative assessment - Ros, Gerard H.; Hoffland, Ellis; van Kessel, Chris; Temminghoff, Erwin J.M. (Soil biology & biochemistry, 2009)
Extractable Organic N (EON) or Dissolved Organic Nitrogen (DON) pools are often analyzed to predict N mineralisation, N leaching, and to evaluate agricultural (nutrient) management practices. Size and characteristics of both pools, however, are strongly influenced by methodology. Quantifying the influence of methodology can increase the accuracy of soil tests to predict N mineralisation, improve model simulations, and can help to quantify the contribution of the EON and DON pools to soil N cycling. We estimated the relative impact of methodological, management, and environmental factors on EON and DON, using a meta-analysis approach based on 127 studies. Our results indicate that the EON and DON pools are neither similar in size nor controlled by the same factors. The influence of factors controlling EON generally decreased in the order of methodology (Δ10–2400%), followed by environment (Δ11–270%) and management (Δ16–77%). DON concentrations were primarily controlled by management factors: different land use and fertilisation caused a variation of 37–118%. Seasonal variations in DON concentrations were generally smaller than variations in EON, suggesting that high mineralisation and sorption rates buffer DON. The large range in EON as affected by different methodology emphasizes the importance of using appropriate and standardized methods for the determination of EON. The determination of DON can be useful to estimate leaching losses. EON, however, can be used to assess the impact of soil management practices on the turnover rate of labile soil organic matter pools.